Microstructure and Wear Properties of Ti-TiC-TiB2 Composite Cladding Deposited on AISI 304 Stainless Steel by Gas Tungsten Arc Process - Somunkiran, Ilyas; Tunc, Busra (Springer, 2023)
In this study, tungsten inert gas (TIG) coating method was used to improve the surface properties of AISI 304 stainless steel. Composite coatings were produced by melting four different ratios of Ti-TiC-TiB2 powders in channels that were 10 mm wide and 1,5 mm deep. The arc current in the TIG coating process was kept constant at 110 A, while the scanning speeds were varied for each sample during the process. The microstructures of the samples were examined using optical microscopy, scanning electron microscope and x-ray diffraction (XRD) techniques. The mechanical properties were analyzed through microhardness measurement and wear test. The microstructure results revealed that the selected welding parameters partially reduced the presence of pores and cracks on the surface, leading to the formation of dendrites. Square and hexagonal TiC/TiB2 phases precipitated between the dendritic arms. The existence of these structures was confirmed by energy-dispersive spectroscopy and XRD data. According to the microhardness results, the highest hardness value was obtained from the Ti-TiC (1:1) sample, while the lowest hardness value was obtained from the Ti-TiB2 (1:1) sample. In the wear test under 10-N load, the Ti-TiC-TiB2 (1:1:2)-based sample exhibited the highest resistance against delamination and adhesive wear.
Keywords: metal matrix composites; stainless steel; TIG coating; titanium; wear